Transvaginal ultrasound-guided methotrexate instillation for failed medical management of ectopic pregnancies in subfertile women - Nikita Naredi; Sumeet Ranjan Tripathy; Rajesh Sharma (Wolters Kluwer Medknow Publications, 2022)
Background: Ectopic pregnancy (EP) defined as extrauterine implantation of the embryo can be managed medically or surgically. Medical management entails systemic administration of the antineoplastic drug methotrexate (MTX) which, if not successful, surgical management is resorted to. However, we carried out this study wherein the failed medical management cases were given intra-gestational sac MTX instead of surgery. Aim: The aim of this study was to assess the efficacy of intra-gestational MTX administration as a treatment modality for failed medical management of ectopic pregnancies. Study Setting and Design: It was a prospective interventional study carried out at the Reproductive Medicine Centre of a tertiary care hospital. Materials and Methods: It was a prospective interventional study wherein 12 patients of EP with failed medical management (as per established criteria) were administered intra-gestational MTX with follicle aspiration needle under transvaginal sonography guidance. Statistical Analysis Used: Data were collected in Microsoft Excel. Numerical continuous variables were expressed as mean ± standard deviation. Categorical variables were expressed as count/percentage. Results: All the patients responded to the local administration of MTX, with none requiring rescue surgery. In addition, no one had any complication of the local instillation. However, one patient required an additional dose of MTX. Conclusion: Intra-gestational MTX administration is a viable non-surgical modality for treatment of ectopic pregnancies even in cases of failed medical management with an added benefit of tubal preservation.